El comportamiento de mercado en la adquisición de vehículos y su influencia en preferencias de marcas de la población de la ciudad de Machala - Cárdenas Luzuriaga, Marielena (2017)
In the present study we investigated the market behavior in the acquisition of vehicles and their influence of brands of the population of the city of Machala, which allowed to somehow know which brand is the one that has more acceptance in the market, that Characteristics see the machaleños before acquiring a vehicle. In recent times, consumers have become more demanding in terms of the products they purchase for that reason, it is necessary to carry out an in-depth analysis of the requirements they have at the moment they wish to acquire a vehicle and thus offer products according to their Needs. Without a doubt, the automotive sector is growing more and more due to the demand of vehicles that exists in different cities of the country, among which is the city of Machala. The present work was accomplished with the main objective that is to know the market behavior in the acquisition of vehicles and the influence of brands in the city of Machala, is based on a bibliographical research carried out in specialized scientific journals that have published topics that have Help for the theoretical development of work, while also conducting field research by conducting interviews and surveys. In addition, a field investigation was applied that allowed to know in depth about the reality of the sale of vehicles in different concepcionias through interviews to the managers of the same, a survey was also made to the clients of the main concepnarias of The city of Machala cooking on aspects related to their preferences of vehicle brands, that is, the reasons why they are inclined to acquire a vehicle of a certain brand and in a certain place. Among the main aspects that stood out are the quality of the vehicle, the guarantees, the price and the attention to the customer that they give them when arriving at a conseccionaria to look for information and purchase options.Finally, the analysis of the study topic was developed, analyzing the economic, political and economic environment together with other factors that influence the decision to buy a vehicle. The automotive market in Ecuador has a wide variety of brands and models of vehicles that generate great competition that exists among companies dedicated to the sale of vehicles of different brands, costs and designs so it is advisable to design strategies that allow to offer services that increase The benefits to the buyer and thus capture a greater number of customers since each customer has preference for certain brands for characteristics that they consider provide benefits and meet their needs.